Himalayan foods: healthy and nutritious crop varieties - Sthapit, B.; Zucker, J.; Bennett, A.; Bioversity International (Bioversity International, 2014)
Brief description of eight underutilized crops in rural Nepal that have become the focus of efforts to promote a healthier lifestyle and marketplace for farmers and locals in Nepal.